The effect of mixing water temperature on concrete properties in hot weather conditions - Assal, Mennatallah Amr (AUC Knowledge Fountain, 2017)
Environmental factors and hot weather conditions can drastically impact the properties, strength and durability of concrete structures. Whereby, higher slump loss rate, faster hydration with accelerated setting, reduced long term compressive strength and plastic shrinkage are more common. Literature review on the impact of hot weather on concrete is not sufficiently elaborated and at the same time majority of studies focused on curing temperature on overall concrete quality, however sufficient research on the effect of casting temperature on the concrete itself and its materials is lacking. This study is carried out to investigate the direct impact of mixing water temperature and concrete temperature on the concrete properties serving in hot weather conditions, with special emphasis to the Egyptian hot climate throughout the year. Thus, the scope of this work is to study mixing water temperature’s impact on concrete properties being a key ingredient to the concrete mix, with direct impact on workability, strength and durability. The feasibility of cooling water as a remedial action in hot climate is covered for various project sizes. To achieve the work objective, four categories of concrete mixtures with various cement contents and admixtures were studied while changing the mixing water temperature at 5, 25 and 45˚C to yield a total 12 different test sets. All other concrete ingredients were heated to 45˚C ahead of mixing to simulate hot weather conditions. Two sets of results were analyzed starting with fresh concrete tests of slump, unit weight and concrete temperature; in addition to hardened concrete tests of compressive and flexural strengths. Results showed an average 15% increase in the 28 days concrete compressive strength and enhanced workability in 5 ˚C temperature water Vs. 45 ˚C suggesting the strong impact of water temperature on concrete properties and need to add cool mixing water to concrete cast in hot weather conditions. Recommendations are provided towards the incorporation of cold water in concrete with a market feasibility conducted to study the technical and economic aspects resulting in up to 9% reduction in concrete cost with cold mixing water incorporated. Keywords : (Water, Concrete, Temperature, Hot Weather, Cooling, Feasibility)